Ornitina alfa-cetoglutarato na isquemia-reperfusäo intestinal em ratos - Gonçalves, Eduardo Silvio Gouveia (2009)
Objective: To evaluate the effect of ornithine alpha-ketoglutarate (OKG) in the blood and intestinal tissue of rats submitted to intestinal ischemia/reperfusion, using the blood concentrations of glucose, G6PDH, pyruvate, acetoacetate, lactate, 3HBDH, glutathione, T-Bars, myeloperoxydase, CPK and LHD, evaluated in vivo on these tissues. Methods: Sixty rats (Rattus norvergicus albinus, Rodentia Mammalia) were selected and aleatorily distributed in five groups of twelve animals, which were: Sham0’(s0’), Sham30’(s30’), Sham60’(s60’), Isquemia(i30’), Reperfusão(r30’). These groups were distributed in subgroups according to the time and the compost used to the “gavagem”. All de animals received the “gavagem” with calcium caseinate or okg, only one dosage, thirty minutes before the exploratory laparotomy (EL). The subgroups s0’Ca, s30’Ca, s60’Ca, i30’Ca and r30’Ca received only calcium caseinate. The subgroups s0’okg, s30’okg, s60’okg, i30’okg and r30’okg received 5g of okg par each kilogram. The samples were taken in five moments: immediately passed the EL; passed 30 minutes of the EL; passed 60 minutes of the EL; passed 30 minutes of the isquemia; passed 30 minutes of the reperfusion. The descriptive statistics were media, error and standard deviation. The values before and after the procedures were compared using the “t” test (“Student pareado” to homogeny and heterogeny variation) and ANOVA. Then, it was used Kolmogorov-Smirnov to compare the normal results. The results were not normal, it was used the Kruskal-Wallis test. Results: It was shown an improvement on the blood lactate(1.186 + 0,18 versus 0,794 + 0,06, p<0,01) to the animals that received okg from i30’. A reduction on blood lactate lactato (0,107 + 0,01 versus 0,266 + 0,02, p<0,05) was noticed in the group r30’ that received okg. It occurred a reduction on plasmatic and tissue pyruvate reduzido (0,146 + 0,24 versus 0,156 + 0,17 and 0,094 + 0,02 versus 0,248 + 0,03, p<0,05) to the group r30’ that received okg. The acetoacetate was reduced to both groups, isquemia and reperfusion, that received okg0,57 + 0,01 versus 0,0685 + 0,01 e 0,128 + 0,04 versus 0,156 + 0,03,*p<0,05). The plasmatic glucose was reduced to the group i30’( 0,1442 + 0,048 versus 1,1098 + 0,0796, *p<0,05) treated with okg and the same happened to the tissue glucose after isquemia (0,1002 + 0,02 versus 0,147 + 0,0264, p<0,05). The LDH had an improvement (0,1002 + 0,02 versus 0,147 + 0,0264, p<0,05) to the group i30’ treated with okg. CPK was reduced (115,13 + 11,77 versus 166,70+6,23,p<0,05) to the group r30’ treated with okg. The tissue glutathione had an improvement to sham okg 30’ (59,17 + 2,39 versus 25,09 + 1.53, p<0,05) and a reduction on isquemia period to the animals treated with okg and CaCa . 3HBDH was reduced (0,062 + 0,01 versus 0,075 + 0,02,p<0,01) in the blood and in the tissues from i30’. This difference was kept to animals’ blood from r30’okg when related to r30’CaCa(0,03 + 0,00 versus 0,0615 + 0,01, p<0,01). There was a reduction on tissue T-BARS to r30’OKG when compared to r30’CaCa(0,0522 + 0,03 versus 0,0745 + 0,02, p<0,05) and an improvement to sham60’CaCa(0,0937 + 0,02 versus 0,020 + 0,01, p<0,01). Glicose and Myeloperoxydase were not affected by the use of okg. All the results were compared to the respective control groups. Conclusion: The used procedures could bring useful results to metabolites in study. The isquemia/reperfusion showed efficiency, offering exogen okg leads to a rising on glicolitic and aerobic activity to tissues and systems. This offer protects yet from the tissue injury and has antioxidant effect during the isquemia/reperfusion injury.